Régimen rimpe-emprendedor en relación con la microempresa en la provincia de El Oro año 2022. - Chiriboga Celi, Ruben Arturo; Leon Salcan, Jorge Alexander (Machala : Universidad Técnica de Machala, 2022)
The present titling work is based on the rimpe-entrepreneurial regime and the microenterprise in the province of El Oro in the year 2022, taking into account the importance of this regime taking into account the obligations of each taxpayer. The purpose of this research is to analyze the number of taxpayers that belong to the Rimpe-Entrepreneur regime and the microenterprise that identifies two elements: income level and labor. On the other hand, considering that the information on taxes was obtained from the database of the Internal Revenue System (SRI), as well as the data from the surveys carried out on a specific number of microentrepreneurs based on the application of a statistical demonstration, the quantitative approach was used. As a result, the methodology used, which was documentary because it supports the different theories discussed on the subject and the level of descriptive research, contributed greatly to the information collected. What was obtained as a result of a number of 1,518,837 taxpayers of the popular entrepreneur-business rimpe regime, in the same way a contribution of 168,405,064 million dollars, being a greater contribution compared to the previous year with the previous regimes as it was the RIM AND RISE
El presente trabajo de titulación se basa en el régimen rimpe- emprendedor y la microempresa en la provincia de El Oro en el año 2022, teniendo en cuenta la importancia que tiene este régimen tomando en cuenta las obligaciones que tiene cada contribuyente. La finalidad de esta investigación es analizar la cantidad de contribuyentes que pertenecen al régimen Rimpe-Emprendedor y la microempresa que identifica dos elementos el nivel ingresos y la mano de obra. Por otro lado, considerando que la información sobre impuestos se obtuvo de la base de datos del Sistema de Rentas Internas (SRI), así como los datos de las encuestas realizadas a un número específico de microempresarios con base en la aplicación de una demostración estadística, se utilizó el enfoque cuantitativo. Como resultado, la metodología utilizada que fue la documental porque sostiene a las diferentes teorías tratadas en el tema y el nivel de investigación descriptiva, contribuyó en gran medida a la información recopilada. Lo que se obtuvo como resultado una cantidad de 1.518.837 de contribuyentes régimen rimpe emprendedor-negocio populares, de la misma manera un aporte de 168.405.064 millones de dólares siendo un aporte mayor a comparación del año anterior con los anteriores regímenes como lo fue el RIM Y RISE.
Keywords: REGIMEN; RIMPE; MICROEMPRESA